Lethal concentrations of the Cypermethrin-containing insecticide to tilapia, Oreochromis Mossambicus fingerlings. - Diaz, Alyssa Jane (UPHSI, 2008)
Farmers venture on rice-fish culture, raising crops together with fishes, and most of them have Oreochromis mossambicus as their fish species because of its high resistance. In this study, Oreochromis mossambicus fingerlings were exposed to different concentrations of Cypermethrin-containing insecticide, which are highly toxic to fishes. The four treatments contained concentrations of 0.0 ppm, 0.25 ppm, 0.38 ppm, and 0.5 ppm. The mortality rate was monitored every three hours for the first 12 hours and every six hours for the succeeding hours, and LC50 and LC99 values were determined for all treatments except Treatment A which was the negative control. The LC50 of the Cypermethrin-containing insecticide after 24 hours of exposure is 0.4 ppm, while the LC99 is 0.9 ppm; however, the LC50 after 48 hours of exposure is 0.2 ppm and the L9 9 is 0.4 ppm. The external sub-lethal effects observed were bulging white eyes, and excretion of a mucus-like substance from the mouth. These were observed from the tilapia fingerlings before they die. The study recommends to the farmers that they should avoid using high concentrations of Cypermethrin-containing insecticides when venturing on rice-fish culture.